Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Belajar Siswa Kelas IV Pada Mata Pelajaran PAI Di SD Negeri 21 Air Amo - Sapitriana, Wela (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students' motivation and learning outcomes in Islamic Religious Education (PAI) by applying the Problem Based Learning (PBL) model in the 4th-grade class of SD Negeri 21 Air Amo. The study was conducted in two cycles, each involving planning, implementation, observation, and reflection. The results showed that the application of PBL could enhance students' learning motivation and outcomes. In the first cycle, students' motivation increased to 50%, and in the second cycle, it reached 66.66%. Despite some challenges, such as some students' inability to understand the material and group collaboration issues, the implementation of this model significantly improved classical completeness. This study suggests the need for further habituation and more intensive guidance for students in utilizing the PBL model